Extended spectrum beta-lactamase detection in gram-negative bacilli of nosocomial origin - Dechen C Tsering (Journal of Global Infectious Diseases, 2009)
Background: Resistance to third generation cephalosporins by acquisition and expression of extended spectrum beta lactamase (ESBL) enzymes among gram-negative bacilli is on a rise. The presence of ESBL producing organisms significantly affects the course and outcome of an infection and poses a challenge to infection management worldwide. Materials and Methods: In the period from June 2007 to 2008, we collected 1489 samples from patients suspected of nosocomial infection. The isolates were identified based on colony morphology and biochemical reaction. Gram negative bacilli resistant to third generation cephalosporins were tested for ESBL by double disc synergy test (DDST- a screening test )and then phenotypic confirmatory test. Antimicrobial susceptibility testing was done by modified Kirby Bauer disc diffusion method. Results: From the sample of 238 gram-negative bacilli, we isolated Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, Citrobacter freundii, Proteus mirabilis, Morganella morganii and Enterobacter cloacae. Following both methods, 34% isolates were ESBL-positive. The ESBL producing isolates were significantly resistant (p < 0.01) to ampicillin, piperacillin, piperacillin/tazobactam, trimethoprim/sulfamethoxazole, tetracycline, ciprofloxacin and gentamicin as compared to non-ESBL producers. Multidrug resistance was significantly (p < 0.01) higher (69.14%) in ESBL positive isolates than non-ESBL isolates (21.66%). Conclusion: High prevalence of ESBL in our hospital cannot be ignored. ESBL producers can be detected by DDST and phenotypic confirmatory test with equal efficacy. The sensitivity of screening test improved with the use of more than one antibiotic and addition of one or two antibiotics would not increase cost and labor. We recommend DDST using multiple antibiotics in all microbiology units as a routine screening test.